Laboratory Scale Seismic Surface Wave Testing for the Determination of Soil Elastic Profiles - Madun, Aziman (International Journal of Integrated Engineering, 2012)
Seismic surface wave testing is well-adapted to the study of elastic parameters and, hence, the elastic profile of soils in the field. Knowledge of a ground’s stiffness profile enables the prediction of ground movement and, thus, the quality of the foundation. The stiffness parameter obtained in this research corresponds to the measurement of the seismic surface wave phase velocity of materials, which relates to the very small strain shear modulus. This paper describes a methodology for performing surface wave testing in the laboratory. In comparison with field tests, a laboratory-scale experiment offers the advantage of allowing the process of data collection to be calibrated, and analytical studies can be carried out as the properties of the material under test are controllable and known a priori. In addition, a laboratory scale experiment offers insight into the interaction between the seismic surface wave, the soil, the boundary and, hence, the constraints associated with the seismic surface wave technique. Two simplified models of different sizes were developed using homogeneous remoulded Oxford Clay (from Midlands region of the UK). The laboratory experimental methodology demonstrated that the seismic surface wave equipment used in the laboratory was directly influenced by the clay properties as well as the size of the test model. The methodology also showed that the arrangement of the seismic source and the receivers had an impact on the range of reliable frequencies and wavelengths obtained.